Recent Advances in the Synthesis of Heterocycles from Oximes - Abele, Edgars; Abele, Ramona (Current Organic Synthesis, 2014)
This review demonstrates that oximes and their derivatives are valuable starting materials for the preparation of many classes of heterocyclic compounds. The main group of reactions includes the cyclization of unsaturated oxime derivatives. Using these starting materials pyrroles, isoxazoles, pyridines and isoquinolines were prepared. Some heterocyclic systems (for example, seven-membered rings) were obtained using the classical Beckmann rearrangement and novel reagents and conditions.
Keywords: five-membered heterocycles